A low profile tunable microwave absorber based on graphene sandwich structure and high impedance surface. Issue 2 (24th October 2019) - Zhang, Jin; Liu, Zhenguo; Lu, Weibing; Chen, Hao; Wu, Bian; Liu, Qifeng
Abstract: In this article, a low profile dynamically tunable microwave absorber is proposed, which consists of high impedance surface and graphene sandwiched structure. We theoretically demonstrate and experimentally verify that the proposed absorber can provide a dynamically tunable reflection range from larger than −3 dB to less than −30 dB at operating center frequency of 11.2 GHz. The entire thickness of this absorber is only 2.8 mm, nearly one tenth of working wavelength. In addition, a modified equivalent circuit model is proposed to explicate its absorption mechanism. At last, we fabricate a prototype absorber, measure its reflection coefficient in anechoic chamber. The experimental results agree well with the full wave simulation results. This work may provide a reference for design and fabrication of dynamically tunable microwave absorber based on large‐scale graphene and may promote the actual applications of graphene at microwave frequency.